Effect on impact properties of adding tantalum to V-4Cr-4Ti ternary vanadium alloy. (June 2022) - Miyazawa, Takeshi; Saito, Haruka; Hishinuma, Yoshimitsu; Nagasaka, Takuya; Muroga, Takeo; Shen, Jingjie; Okuno, Yasuki; Yu, Hao; Kasada, Ryuta; Hasegawa, Akira
Highlights: Effect of Ta addition on the Charpy impact properties of V-4Cr-4Ti alloy was investigated. Both the upper shelf energy and the ductile–brittle transition temperature increased with increasing Ta content. The addition of 3 wt.% Ta resulted in solid solution strengthening without any degradation of the Charpy impact properties. Abstract: Four V-Ta-4Cr-4Ti quaternary alloys containing different quantities of Ta were investigated to determine the effect of Ta content on the Charpy impact properties. Five button-shaped ingots of the V-4Cr-4Ti ternary alloy and V- x Ta-4Cr-4Ti quaternary alloys ( x = 3, 9, 15, and 22 wt.%) were fabricated on a laboratory scale by using non-consumable arc-melting in an argon atmosphere. Charpy impact tests were conducted at temperatures ranging from 77 K to 293 K using an instrumented impact tester. Both the upper shelf energy and the ductile–brittle transition temperature increased with increasing Ta content. The addition of 3 wt.% Ta resulted in solid solution strengthening without any degradation of the Charpy impact properties. Thus, the addition of 3 wt.% Ta (V-3Ta-4Cr-4Ti) is an appropriate amount to use in blanket structural materials for nuclear fusion reactors. The spectra of TEM-EDS for V-3Ta-4Cr-4Ti quaternary alloy indicate that there is no significant enrichment of Ta in the matrix as compared with that in the precipitate. However, thermal aging may result in the formation of the Laves phase, causing the degradation of Charpy impact properties. The characterization of precipitates, thermal aging, and creep tests of the V-3Ta-4Cr-4Ti quaternary alloy need to be investigated to determine the optimum Ta content.